Answer:
P[(X=n+k)] ∩ X>n)] =P[X=K]
Explanation:
If X is a geometric random variable then
for success probability = p
so for failure q= 1-p
Now as given
![P_(x)(n)=(1-p)^(x-1)P_{}](https://img.qammunity.org/2020/formulas/mathematics/high-school/2d38k2yvvv8lo6a4yzh9tboo31ufqiyddy.png)
Now for the P parameter we have
x∈{1,2,3,....∞}
![P [X=K] = (1-P)^(K-1)P_{}](https://img.qammunity.org/2020/formulas/mathematics/high-school/ostzy9ww5zko4wjpqb8vmqp6px43fu88px.png)
![P [X=n+K] = (1-P)^(n+K-1)P_{}](https://img.qammunity.org/2020/formulas/mathematics/high-school/kadubrchiqaglnze0jax3weuc629aarjfp.png)
![p[(X=n+K)/(X>h)]=([(X=n+K)n,X>n])/(P(X>n))](https://img.qammunity.org/2020/formulas/mathematics/high-school/67lg06axl68ye7ua3vswpt9fpujt2lyynk.png)
![P(X>n)=\sum_(i=n+1)^(\infty)(1-P)^(i-1)P^{} \\](https://img.qammunity.org/2020/formulas/mathematics/high-school/uugq6ikro4sir7o76pja277e7pferxgc5k.png)
![P(X>n)=P\sum_(i=n+1)^(\infty)(1-P)^(i-1)^{}](https://img.qammunity.org/2020/formulas/mathematics/high-school/orvbqilxmjwe0d0mwbka67m6gcglpq35sd.png)
![P(X>n)=P(1-P)/(1-(1-P)^(n) ) =(1-P)^(n)](https://img.qammunity.org/2020/formulas/mathematics/high-school/srf5tjxi46bzyu1o586tnpa5oxv19vriqr.png)
P[(X=n+k)] ∩ X>n)] = P(X=n+K)
P[(X=n+k)] ∩ X>n)] =
![((1-P)^(n+k-1)P )/((1-P)^(n) )](https://img.qammunity.org/2020/formulas/mathematics/high-school/vpgehyaqtewb7vjwnf00ok32rctxsq1xax.png)
P[(X=n+k)] ∩ X>n)] =
![(1-P)^(k-1) .P](https://img.qammunity.org/2020/formulas/mathematics/high-school/vdmlblz3gvv46zzmq25r05puwb4bgenrsi.png)
P[(X=n+k)] ∩ X>n)] =P[X=K]